EFEKTIVITAS PENDEKATAN QUANTUM LEARNING DAN CONTEXTUAL TEACHING AND LEARNING (CTL) TERHADAP PRESTASI BELAJAR MATEMATIKA DITINJAU DARI POLA ASUH ORANG TUA SISWA SMP DI KABUPATEN MAGETAN TAHUN AJARAN 2012/2013 - Lusiana, Restu (Jurnal Pembelajaran Matematika, 2013)
ABSTRACTThe objectives of the research are to investigate: (1) which learning approach of the quantum learning approach with discussion method, the contextual teaching and learning with discussion method, and the direct learning method results in a better learning achievement; (2) which students of those with authoritarian, democratic and permissive parenting patterns have a better learning achievement; (3) in each approach, which students of those with authoritarian, democratic, and permissive parenting have a better learning achievement; (4) in each type of parenting patterns, which learning approach of the quantum learning approach with discussion method, the contextual teaching and learning with discussion method, and the direct learning method results in a better learning achievement results in a better learning of achievement. This research used the quasi experimental research method with the factorial design of 3x3. The population of the research was the students in Grade VII of State Junior Secondary Schools in Magetan regency in Academic Year 2012/2013. The samples of the research were taken by using the stratified cluster random sampling technique. The data of the research were gathered through documentation method, questionnaire of parenting patterns, and test of learning achievement. The data of the research were analyzed by using unbalanced two-way analysis of variance. The results of the research are as follows. 1) The quantum learning approach results in a better learning achievement than those with the contextual teaching and learning approach or the direct learning approach, but the contextual teaching and learning approach results in a better learning achievement than the direct learning. 2) The students with the authoritarian parenting pattern have the same good learning achievement as those with the democratic parenting pattern or those with the permissive parenting pattern, but the students with the democratic parenting pattern have a better learning achievement than those with the permissive parenting pattern. 3) In each parenting pattern, the quantum learning approach with the discussion method results in a better learning achievement than the contextual teaching and learning with the discussion method or the direct learning method. 4) In each learning approach, the students with the authoritarian parenting pattern have the same good learning achievement in Mathematics as both those with the democratic parenting pattern and those with the permissive parenting one. Yet, the students with the democratic parenting pattern have a better learning achievement in Mathematics than those with the permissive one.Keywords: Quantum learning, contextual teaching and learning, parenting patterns, and learning achievement in Mathematics